2017
DOI: 10.25186/cs.v12i2.1268
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescência transiente da clorofila a e crescimento vegetativo em cafeeiro conilon sob diferentes fontes nitrogenadas

Abstract: O uso de fertilizantes nitrogenados é um recurso eficaz para elevar a produtividade do cafeeiro, de modo que o aprimoramento e/ou geração de novas técnicas que auxiliem no manejo da adubação nitrogenada são fundamentais, pois contribuirão para aumentar a eficiência de uso do nitrogênio (N). Dessa forma, objetivou-se determinar a fluorescência transiente da clorofila a e o crescimento vegetativo do cafeeiro Conilon sob diferentes fontes nitrogenadas. O experimento foi realizado em Nova Venécia - ES - Brasil, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Freire et al (2019) evaluated chlorophyll a, b, and total in Crespa lettuce in different crop seasons in Palmas, Tocantins, Brazil, and found higher values, with mean chlorophyll a of 13.72 μg g -1 and 14.33 μg g -1 , respectively, for conventional and organic crop systems. Chlorophyll a is a main photosynthetic source, responsible for conversion of light into chemical energy in plants (OLIOSI et al, 2017). In the present study, a higher chlorophyll a than chlorophyll b was found (Table 4), which confirms the results of Rosa et al (2014), who reported a higher abundance of chlorophyll a, corresponding to approximately 75% of green pigments in plants.…”
Section: Resultssupporting
confidence: 91%
“…Freire et al (2019) evaluated chlorophyll a, b, and total in Crespa lettuce in different crop seasons in Palmas, Tocantins, Brazil, and found higher values, with mean chlorophyll a of 13.72 μg g -1 and 14.33 μg g -1 , respectively, for conventional and organic crop systems. Chlorophyll a is a main photosynthetic source, responsible for conversion of light into chemical energy in plants (OLIOSI et al, 2017). In the present study, a higher chlorophyll a than chlorophyll b was found (Table 4), which confirms the results of Rosa et al (2014), who reported a higher abundance of chlorophyll a, corresponding to approximately 75% of green pigments in plants.…”
Section: Resultssupporting
confidence: 91%
“…The addition of saffron when cooking rice can be a great alternative to increase the general population's daily consumption of anthocyanins, given that anthocyanin is also a type of antioxidant, which is known as a plant-derived bioactive compound, thus promoting health, slowing the aging process and preventing disease. As a result, antioxidant constituents in plant material awakened the interest of scientists, food manufacturers, cultivators, and consumers due to the role they play in maintaining human health [35][36][37][38][39][40][41]. Although carotenoids are widely distributed in fresh saffron systems, analyses have only focused on some compounds that are involved in aspects of human health, considering that in biological systemsespecially the human systemthey behave as antioxidants and prooxidants, under different conditions; besides, α-carotene and β-carotene are precursors of retinol biosynthesis (vitamin A).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Economic factors related to the production process make urea the most used nitrogen fertilizer in world agriculture (Silva et al, 2011). Due to the easily acquisition, high concentration of N, lower cost per kilogram of N, low corrosivity, and high solubility, urea is the most used source of N in C. canephora crops (Oliosi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%